Independently Certified Industry‐specific Disclosures to the Capital Market: The JORC Code in the Australian Mining Industry. - Katselas, Dean; Sidhu, Baljit K.; Smith, Tom; Yu, Chuan (Abacus, 2019)
We investigate compliance with the Australian JORC Code for reporting mineral resources and ore reserves, the quality of the disclosure, and its impact on the capital market. The compliance and quality assessment is conducted by two experienced geologists who find that while the overall reporting quality improved after the 2012 revisions to the Code, they disagree on the extent of improvement. This reflects the uncertainties involved and the difficulty in interpreting the reports. Both geologists agree that the greatest improvement is seen in early‐stage projects, consistent with the expectation that there are more uncertainties surrounding these, and the additional information disclosed under the 2012 JORC Code appears to assist in reducing the uncertainties to some extent. The capital markets study shows that JORC announcements have a significant impact on investors' assessments of firm value, and that the announcement impact is higher after the 2012 revisions designed to strengthen the disclosure requirements. This is consistent with post‐2012 JORC reports conveying higher information content. There continues to be information leakage prior to announcement date. Further tests show a widening of bid–ask spreads in the post‐2012 period, suggestive of higher information asymmetry. While the probability of informed trading declines for large firms, it remains statistically unchanged for the rest of the sample. The findings reiterate the need for regulators and standard setters to be cognisant of unintended consequences of their decisions. The substantiation process under JORC involves a delay in the release of 'news', a 'chilling' effect with larger announcement effects.